RIG-I-Like Receptor-Mediated Recognition of Viral Genomic RNA of Severe Acute Respiratory Syndrome Coronavirus-2 and Viral Escape From the Host Innate Immune Responses - Kouwaki, Takahisa; Nishimura, Tasuku; Wang, Guanming; Oshiumi, Hiroyuki (Frontiers in Immunology, 2021)
RIG-I-like receptors (RLR), RIG-I and MDA5, are cytoplasmic viral RNA sensors that recognize viral double-stranded RNAs and trigger signals to induce antiviral responses, including type I interferon production. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) caused the coronavirus disease 2019 pandemic. However, the RLR role in innate immune response to SARS-CoV-2 has not been fully elucidated. Here, we studied the roles of RLR in cytokine expression responding to SARS-CoV-2 and found that not only MDA5 but also RIG-I are involved in innate immune responses in some types of human cells. Transfection of total RNAs extracted from SARS-CoV-2-infected cells into epithelial cells induced IFN-β, IP-10, and Ccl5 mRNA expression. The cytokine expression was reduced by knockout of either RIG-I or MDA5, suggesting that both proteins are required for appropriate innate immune response to SARS-CoV-2. Two viral genomic RNA regions strongly induced type I IFN expression, and a 200-base fragment of viral RNA preferentially induced type I IFN in a RIG-I-dependent manner. In contrast, SARS-CoV-2 infectious particles hardly induced cytokine expression, suggesting viral escape from the host response. Viral 9b protein inhibited RIG-I and MAVS interaction, and viral 7a protein destabilized the TBK1 protein, leading to attenuated IRF-3 phosphorylation required for type I IFN expression. Our data elucidated the mechanism underlying RLR-mediated response to SARS-CoV-2 infection and viral escape from the host innate immune response.